The executive's guide to 21st century corporate citizenship : how your company can win the battle for reputation and impact - Stangis, Dave; Smith, Katherine Valvoda (Emerald Publishing Limited, 2017)
The Executive's Guide to 21st Century Corporate Citizenship is a succinct handbook that provides senior managers with everything they need to understand how corporate citizenship builds reputation, delivers value to the bottom line, and mobilizes an organization's employees and customers. It shows how integrating sustainability and social impact to improve your operating context can also improve your company's competitive position, and steers readers through the field of corporate citizenship to provide actionable insights based on empirical research. The book features tools that will prove valuable for every business person thinking about how to maximize business and social value, while the concepts addressed in the book are essential for executives leading manufacturing B2B or B2C companies that are managing complex supply chains, integrated operations, and corporate reputation. This book provides a major update on how to 'do' corporate citizenship and will help you win the reputation battle and deliver value to society while creating the most successful business possible in today's competitive landscape.- Resumé vydavatel
Obsahuje index.
Keywords: společenská odpovědnost firem -- 21. století; manažerská etika; corporate social responsibility -- 21st century; business ethics; příručky; elektronické knihy; handbooks and manuals; electronic books